Collapsible kitchen cabinet for small house usage / Muhammad Fitri Samsuddin … [et al.] - Samsuddin, Muhammad Fitri; Mohd Anwar, Mohd Firuz; Mohd Yusof, Nurhikma; Samsudin, Nazashah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
To design a collapsible kitchen cabinet which can be moved and transformed in different arrangement based on limited kitchen layout, multifunctional with new style and concept in design in order to suit the problem of limited space at the kitchen area. The objective of the design is to tackle the problem of limited space at the kitchen area especially for those who live at the low cost apartment or condominium. The advantages of this new invention and concept of the collapsible kitchen cabinet are it can be transformed and rearrange in different design according to the limited kitchen area layout. Basically, it has four separated part which different from the existing kitchen cabinet. In term of commercialization, this collapsible kitchen cabinet will get the positive support from the society, furniture industry, manufacturer, economy and the main is the user especially for those who newly marry, young couple, a bunch of bachelor which lives at the low cost apartment or condominium.